Influence of montane altitudinal ranges on species distribution models; evidence in Andean blow flies (2020)
Background. Blow flies are a family of dipterans of medical, veterinary and sanitary importance. We aim to predict the current geographical distribution of six neotropical blowfly species with different altitudinal ranges of distribution (high, medium, and lowlands) and degree of synanthropy (eusynanthropic, hemisynanthropic and asynanthropic) based on their existing fundamental niche (EA) in Northwestern South America. Methods. Geographical records were compiled based on data from museum specimens and literature. The accessible area hypothesis (M) was calculated based on three criteria: (1) Altitudinal range, (2) Synanthropy values deducted based on the Human Influence Index (HII) raster dataset, and (3). The mean dispersal capability of flies. The modeling was performed using the Maxent entropy modeling software. The selection of parameters was made with the R Program ENMeval package. Results. The models were assessed using the area under the operator-partial receiver curve (ROCp). The high statistical performance was evidenced in every modeling prediction. The modeling allowed identifying possible taxonomic inaccuracies and the lack of exhaustive collection in the field, especially for lowlands species. Geographical distribution predicted by the modeling and empirical data was remarkably coherent in montane species. Discussion. The data obtained evidence that montane elevational ranges affect the performance of the distribution models. These models will allow a more precise predicting of medium and high elevation blow flies than lowlands species. Montane species modeling will accurately predict the fly occurrence to use such biological information for medical, legal, veterinary, and conservation purposes.